Answer:
Answer E. is correct
Step-by-step explanation:
b = 3 * c --> c = 1/3 * b
c + 3 = 1/3 * b + 3 --> E.
Steps to solve:
3^2 • 3^-8 • 3^0
~Apple exponent rule [ a^b * a^c = a^b+c ]
3^2-8+0
~Simplify
3^-6
~Use exponent rule [ a^-b = 1/a^b ]
1/3^6
~Simplify
1/729
Best of Luck!
The correct answer among all is D. I'm in K12 8th grade by the way so nice to meet you :)
<em>3 minus ___</em> ⇒ 3 - ___
<em>the product of 2 and a number x</em> ⇒ 2x
"3 minus the product of 2 and a number x" ⇒ 3 - 2x
_____
Each part of the description has a translation.